Total Quality Management as a Strategic Driver for Sustainable Performance: Evidence from Bangladesh’s Banking Industry - Islam, Nafiza; Sehreen, Farhana; Polas, Mohammad Rashed Hasan (Electronic Journal of Business and Management, 2025)
This study aims to examine and discuss the critical success factors of TQM influencing the sustainable organizational performance in the banking industry of Bangladesh. Following a FGD with mid-level bankers and comprehensive literature review, a questionnaire has been designed and checked the reliability by academicians, research scholars, and field experts of this sector. 150 questionnaires were distributed, and the data were scrutinized and summarized through Partial Least Square-based Structural Equation Modelling PLS-SEM. The study result supported that top management leadership; continuous improvement and organizational culture have significant impact on sustainable organizational performance. However, the study uncovered a significant lacking regarding TQM practices in this sector, particularly, the inadequate attention afforded to customer relationship and supplier partnership. In the context of Bangladesh, TQM practice is relatively a newfangled idea and critical success factors of TQM are not well-informed or well-understood. The insights of this study are expected to contribute to understanding the significance of incorporating the critical success factors of TQM as strategic initiatives from top management to frontline.